Advokasi Dinas Lingkungan Hidup untuk Meningkatkan Partisipasi Masyarakat dalam Pengelolaan Sampah di Kota Padang - Sepvani, Nadira; Adnan, M. Fachri (YASIN, 2025)
This research explains the environmental agency's advocacy to increase community participation in waste management in Padang City as well as the factors inhibiting the environmental agency's advocacy to increase community participation in waste management in Padang City. This study uses a qualitative descriptive methodology. Observations, interviews and documentation studies were used to collect data. Participants selected using purposive sampling included employees from the Padang City Environmental Service, Waste Bank Managers, and the community. To ensure the validity of this research data, source triangulation and method triangulation methods were used, and interactive models were used to analyze the data. The results of the research show that the environmental department has not done much to encourage people to become more involved in waste management in Padang City. Implementation of environmental policy advocacy to increase community participation in waste management aims to build awareness, change behavior and create policies that support effective waste management. Implementation of environmental policy advocacy uses various strategies, including educational outreach, formation of waste banks, collaboration with stakeholders, use of social media and mass media. The inhibiting factors for advocacy in increasing community participation in waste management in Padang City are lack of public awareness and knowledge, limited infrastructure and facilities, limited budget.